The Influence of Transformational Leadership, Quality of Human Resources and Work Discipline on Employee Performance - Dewi, Anisa Indah Lestari; Krisnandi, Herry; Digdowiseiso, Kumba (Ridwan Institute, 2024)
The aim of this study was to scrutinize the impact of leadership transformation, HR quality, and work discipline on employee performance at PT Pegadaian Galeri 24. Primary data, collected through questionnaires from 94 respondents at PT Pegadaian Galeri 24, formed the basis of this research. The findings from the partial survey indicate that leadership transformation, HR quality, and work discipline all exhibit positive effects on employee performance, contributing significantly to their overall effectiveness. This study serves as a valuable reference and input for enhancing the quality of human resources at PT Pegadaian Galeri 24. It suggests that improving employee performance can be achieved by focusing on refining leadership, HR quality, and work discipline. Including a brief sentence about potential areas for future research based on the study's findings could provide a forward-looking perspective and highlight avenues for further exploration in the field.